Application of FFT transformation and coherence analysis to identify the slow-changing cyclical component on the housing market - Mach, Łukasz; Zmarzły, Dariusz; Dąbrowski, Ireneusz; Frącz, Paweł (Zastosowanie transformacji FTT oraz analizy koherencji do identyfikacji składowej cyklicznej wolnozmiennej na rynku budownictwa mieszkaniowego, 2020)
The paper reports the results of a study concerned with the identification and definition of time and frequency parameters regarding the cyclical phenomenon on the housing construction market. The cyclical component analysis in the frequency domain was identified using fast Fourier transformation, while the identification of the cyclical component and the interdependence of variables was performed by application of coherence analysis. The research provided answers to the questions regarding active cyclical characteristics that form determinants affecting the condition of the housing market. The resulting knowledge can be useful in decision-making processes that take place in the housing construction market, both on the demand and supply side of this market, as well as helpful in assessing the anticipated prices on the housing market and the formation of speculative bubbles
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 10, s. 55-68